Effect of Multimedia in the teaching of Geotectonic and its satisfaction level on class VIII students - Dutta, Sharmila; Ghosh (Gayan), Sanghamitra (Indian Journal of Educational Technology, 2022)
Research in Teaching–learning process through Multimedia shows many factors affect students’ performance. Therefore, the present study aimed to know the problems faced by class VIII students of Bengali Medium School of West Bengal in learning Geotectonic. The purpose of the present study was to know the effect of Multimedia in teaching Geotectonic to class VIII students and to know their satisfaction level of them in Kolkata and Purba Medinipur District. Researchers aimed to study whether there is any significant difference between the effect of Multimedia in teaching and student’s achievement with respect to teaching Geotectonic among class VIII students. All students of class VIII in Bengali Medium Schools of West Bengal Board are considered as the population of the study. The sample comprises 320 students. To assess the effect of Multimedia on teaching, researchers used self-made parallel form tests of achievement and an opinionnaire for students’ satisfaction levesl. An Experimental Survey design has been chosen to conduct the present study. The findings of the study revealed that the majority of students achieved high score performance, after the treatment phase. The study also indicates that there exists a significant and positive effect of Multimedia among class VIII students of Kolkata and Purba Medinipur.